Spontaneous splenic rupture, an unusual presentation of tuberculosis - Edson R. Marcos-Ramírez (Permanyer, 2021)
Introduction: Spontaneous splenic rupture from tuberculosis (TB) is a very unusual presentation within the wide range of presentations of this infectious disease. Clinical case: A 40-year-old male with a diagnosis of human immunodeficiency virus, begins with fever and pain in the left hypochondrium. A computed tomography scan was performed, showing probable splenic abscesses; suddenly, it begins with hemodynamic deterioration, exacerbation of pain, a surgical exploration was performed, showing spontaneous splenic rupture. Microscopic study of the spleen shows the presence of Mycobacterium tuberculosis. Conclusions: This is yet another presentation of TB, which can become a surgical emergency.